Application of Scaffolding-based Learning Media PhET Simulation in Improving Student Learning Outcomes at SMA Negeri Ambulu - Khoirul Anwar; Laily Ramadhanty; Yushardi (Experimental Student Experiences, 2023)
Computergsimulation is an alternative and effective solution in understanding physics concepts that are difficult to describe through laboratory experiments. One of the platforms that provide experiments in the form of simulations is a virtual laboratory. One of the virtual laboratory applications is PhET Simulation. In this study, based on research on the application of virtual lab-based learning media PhET Simulation for students in class X-6 SMA Negeri Ambulu on the topic of Global Warming. This study uses two parameters, namely the experimental class and the control class. The data of this study were obtained from the results of the pretest and posttest using the Learners' Worksheet which was tested using normalized gain. Based on the research that has been done, the results of the normalized gain value of the experimental class are 0.64. While the control class normalized gain value is 0.14. From this N-gain value it can be concluded that student learning in experimental classes with the help of virtual lab PhET Simulation can increase more significantly than student learning in control classes that do not use virtual lab PhET Simulation.